Impacts of tailored plot-level agricultural extension and crop insurance services based on pictures - Kramer, Berber (American Economic Association, 2023)
Improving the timeliness and relevance of agricultural extension through the use of mobile phones and localized weather information has improved agricultural practices among smallholders in many parts of the world. The proliferation of smartphones in developing countries provides an opportunity to further tailor advisories by utilizing sophisticated media and allowing for better engagement between farmers and extension providers. We test the impacts of picture-based advisories, low-cost, plot-level, interactive advisory service based on ground images sent by farmers of individual fields. We conduct a cluster randomized trial in India and Kenya to evaluate impacts of these image-based remote advisories on knowledge, technology adoption, and farming outcomes, while assessing heterogeneity in returns and underlying behavioural mechanisms. In addition to advisories, we provide access to plot-level picture-based insurance (PBI), to further enhance agricultural risk management and adoption of recommended practices, and test whether the tailored advisories contribute to reducing information asymmetry problems in PBI.